PENGARUH STATUS SOSIAL EKONOMI KELUARGA TERHADAP PRESTASI BELAJAR SISWA DI SD INPRES LIMBUNG KECAMATAN BAJENG KABUPATEN GOWA - Nurislamiah; Kaharuddin; Try Gustaf Said (STKIP Subang, 2025)
This research is motivated by students who are lazy and often ignore the assigned school assignments. The purpose of this study is to determine the influence of family socioeconomic status on student learning achievement at SD Inpres Limbung, Bajeng District, Gowa Regency. This research is a quantitative study with an exploratory design analysis of the product moment correlation coefficient. The population in this study were 43 fifth grade students, the sample taken from class VA using a purposive sampling technique of 22 students consisting of 13 girls and 9 boys. Data were collected through questionnaires and documentation techniques. The results of this study indicate that the four indicators of family socioeconomic status have a significant relationship with student learning achievement. The level of education and type of parental employment contribute to student learning patterns and motivation, while family income and wealth influence the availability of learning facilities that support academic success. From the results of calculations using the product moment formula, the rxy value is greater than rtable at a significance level of 5% (0.933 > 0.444) and at a significance level of 1% (0.933 > 0.561). This means that there is a